2009
DOI: 10.2215/cjn.02760409
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TWEAK Plasma Levels as a Novel Biomarker of Endothelial Function in Patients with Chronic Kidney Disease

Abstract: Background and objectives: Recently, we showed that soluble TNF-like weak inducer of apoptosis (sTWEAK) plasma levels are diminished in hemodialysis patients and had additive effects with IL-6 on survival. Because sTWEAK plasma level has been associated with the presence of chronic kidney disease (CKD) and cardiovascular disease, we hypothesized that in patients with CKD, sTWEAK levels may relate to the increased prevalence of endothelial dysfunction that usually accompanies the decline of estimated GFR (eGFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 43 publications
8
74
1
2
Order By: Relevance
“…Alike in non-renal individuals, 6 studies have shown that low sTWEAK levels are related to atherosclerosis, endothelial dysfunction, and prediction of cardiovascular events in non-CKD patients and nondialyzed CKD stages. 7,8 Confusingly, high levels have also been shown to relate to atherosclerosis, vascular calcification, and mortality in dialysis individuals, 9,10 suggesting a dual or time-differential effect that agrees nevertheless with observations in non-CKD patients. 11 Fibroblast growth factor-23 (FGF-23) is an emerging mediator of the vascular calcification process.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Alike in non-renal individuals, 6 studies have shown that low sTWEAK levels are related to atherosclerosis, endothelial dysfunction, and prediction of cardiovascular events in non-CKD patients and nondialyzed CKD stages. 7,8 Confusingly, high levels have also been shown to relate to atherosclerosis, vascular calcification, and mortality in dialysis individuals, 9,10 suggesting a dual or time-differential effect that agrees nevertheless with observations in non-CKD patients. 11 Fibroblast growth factor-23 (FGF-23) is an emerging mediator of the vascular calcification process.…”
Section: Introductionsupporting
confidence: 69%
“…FGF-23 is a hormone that is secreted from osteoblasts with phosphaturic effects. FGF-23 levels progressively increase as CKD advances 8 and is restored following a successful transplantation. 15 Several studies have investigated the relationship between FGF-23 and carotid atherosclerosis in dialysis patients; reporting controversial results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, lower plasma sTWEAK has been reported in subjects with subclinical atherosclerosis, diabetic subjects, CKD patients (18 -20,36), and in this study. In CKD patients, sTWEAK appeared to be robustly and negatively associated with ED (19), and sTWEAK plasma concentrations were good prognosticators of all-cause and CVD mortality in patients undergoing hemodialysis (18). Interestingly, in patients with chronic stable heart failure, reduced sTWEAK levels predicted an adverse prognosis independently of established risk markers such as the N-terminal prohormone of brain natriuretic peptide (37) and contributed to improve the prediction of coronary artery disease (38).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of TWEAK to its receptor, Fn14 (13), mediates multiple biologic effects such as cellular growth, proliferation, and migration; osteoclastogenesis; angiogenesis; and apoptosis (15)(16)(17). sTWEAK plasma levels decrease with impaired renal function and associate with the aggravation of the endothelial function and the mortality risk (18,19). In the same line, diminished sTWEAK levels have been reported in patients with subclinical atherosclerosis (20).…”
mentioning
confidence: 90%